Verification of selected methods of body height prediction for male and female pupils on the example of students of the Upper Secondary School Complex No. 2 in Dąbrowa Tarnowska, Poland - Orwat, Patryk; Żarów, Ryszard (Health Promotion & Physical Activity, 2025)
Aim: The aim of the study was to assess the magnitude of error in the prediction of adult body height of male and female pupils from the Upper Secondary School Complex No. 2 in Dąbrowa Tarnowska using the Roche-Wainer-Thissen, Khamis-Roche and Żarów methods. Material and methods: Data on the height and weight of 101 18-year-old pupils (54 female pupils and 47 male pupils), as well as parental mean body height, were used in the study. The pupils’ height and weight data came from screening tests performed at 6.5, 10 and 12 years of age by nurses and school hygienists, while the data on parents’ height was obtained through written notes provided by the students. Results: An evaluation of the prognostic methods carried out showed differences in prognostic performance depending on the method, the age of the predicted body height and gender. An analysis of the distribution of the absolute error of prognosis at the age of 10 showed that as many as 71% of all prognoses showed an error of less than 3 cm in relation to the actual body height at age 18, which should be considered a very good result in clinical or school practice setting. Conclusion: Based on the analysis of the results, it was found that models based on data from the ages of 10 to 12 years provided the highest accuracy for predicting adult body height. The Żarów Model for male pupils and the Khamis-Roche Model for female pupils show the lowest mean prediction error. The models are the most accurate for individuals with a typical developmental trajectory, and their performance decreases in extreme cases (very tall and very short children).